Puasa dan Kesehatan Fisik : Kajian Medis - Binti Khoirur Rofiah; Syamsurizal Yasid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Fasting involves refraining from actions that would invalidate the fast, with the intention of observing it from sunrise to sunset. When practiced with sincerity, fasting offers not only spiritual rewards but also the potential for the forgiveness of past and future sins. Research suggests that fasting provides a beneficial rest period for the digestive system, including enzymes and hormones, which typically remain active in digesting food. This constant activity, when not fasting, may lead to various health complications, such as skin conditions, premature aging, and cardiovascular issues. Additionally, fasting can serve as a means of overcoming sinful behaviors, helping individuals return to their innate human state.